The Performance of by Turns Fermentation- Dryer for Vanilla (Vanilla Planifolia Andrews) Processing - Sitti Nur Faridah; Abdul Waris; Haerani Haerani (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2011)
The drying and fermentation are the processing steps which influence the quality of vanilla. Thus, an effort to produce instrument which can dry and ferment vanilla by turns automatically was done. Based on the test result on the instrument, it was known that the heater and heat-exchanger can function excellently. It can be seen from the increase of temperature after passing heater and heat-exchanger; and the decrease of air humidity in the drying chamber. The small differences of air flow speed between racks proved the uniformity of air flow speed in the drying chamber. The time and temperature control system showed temperature stability on drying process (i.e. 60°C) and on fermentation process (i.e. 40°C); moreover, temperature response reached 60°C and did not exceed the setting time (maximum 30 minutes). The water percentage depletion from 88% to 55% is relatively slow (in 5 days fermentation-drying process). The depletion is appropriate with the recommendation for fermentation-drying vanilla processing.